STUDY ON THE TWO-DIRECTIONAL RELATIONSHIP BETWEEN MYASTHENIA GRAVIS AND PREGNANCY - Djordjevic, Gordana; Stojanov, Aleksandar (Acta medicae Medianae, 2022)
Due to the high prevalence of myasthenia gravis (MG) in women of reproductive age, pregnancy in patients with MG is not uncommon. This requires special clinical and therapeutic caution. There is a two-way relationship between MG and pregnancy: Pregnancy can affect the course of the disease, but MG can affect childbirth and the occurrence of postnatal complications. The purpose of our study was to evaluate the clinical course, delivery, and neonatal outcome of pregnant women with the diagnosis of myasthenia gravis. The clinical course of the disease during pregnancy, labor, and postpartum period was reviewed, as well as the neonatal period in the 23 infants born to 15 MG mothers. Spontaneous abortion was observed in two pregnant women (8%) in the second month of pregnancy. One newborn was diagnosed with transitory neonatal MG. There were no stillbirths or physical anomalies. Clinical worsening was recorded during 10 pregnancies (40%), in 8 pregnant women. The clinical course of MG in pregnancy is variable and unpredictable, but pregnancy does not affect the long-term course of MG. Spontaneous abortion is a potential complication in pregnant women with MG. Cesarean section is a more frequent intervention in pregnant women with MG compared to the general population of women. Thymectomy in mothers with MG before pregnancy could potentially have a positive benefit for the newborn. Neonatal transient myasthenia was uncommon in our patient population. No congenital abnormalities were discovered in the 23 babies delivered at our institution.